Current collector, electrode plate and lithium ion battery
By forming auxiliary coatings on both sides of the current collector body of the lithium-ion battery, the lithium embedded capacity and infiltration performance of the battery are improved by using ionic conductive agents and carbon material conductive agents, the problems of fast charging and long-life performance of lithium-ion batteries are solved, and the problem of fast charging and long-life performance of lithium-ion batteries is achieved. Lower electrode impedance and higher energy density.
Patent Information
- Application Number
- CN202411730841.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium-ion batteries have challenges in fast charging and long-life performance, especially the insufficient lithium-embedding and infiltrating performance of the negative electrode, resulting in high impedance, low cycling performance, and insufficient thermal conductivity when thermal runaway, affecting battery safety.
The auxiliary coating formed on both sides of the current collector body includes ionic conductive agents and carbon material conductive agents, and controls their mass ratios within the range of 0.2~20 to improve the contact strength between the active material and the current collector and the wetting performance of the electrolyte. Reduce the electrode impedance and control the short-circuit current through the carbon material conductive agent to prevent thermal runaway.
It improves the fast charging performance, low temperature performance and cycling performance of lithium-ion batteries, reduces the amount of binder, enhances battery stability and energy density, improves the thermal runaway control of the battery, and extends battery life.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a current collector, an electrode plate and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have the advantages of high operating voltage, wide operating temperature range, high energy density, high output power, no memory effect and long cycle life. They are not only widely used in 3C digital products such as mobile phones and laptops, but also have a broad application market in new energy vehicles and large-scale energy storage. Especially in the new energy vehicle and energy storage industries, the requirements for fast charging and long life performance of lithium-ion batteries are increasing.
[0003] For fast charging, the key is to improve the lithium insertion capacity of the negative electrode. There are many factors that affect the lithium insertion capacity of the negative electrode graphite, one of which is the influence of the negative electrode binder content. Since the impedance of the binder is high, the higher the binder, the greater the impedance, so it is urgent to reduce the binder content; but reducing the binder content will cause the bonding ability between the negative electrode active material and the copper foil to deteriorate, resulting in the loss of the negative electrode sheet.
[0004] For long-life performance, the wettability of the negative electrode is the main influencing factor, especially under the conditions of high surface density and high compaction. How to improve the wettability of the negative electrode sheet and ensure the battery life is also a key point that needs to be improved.
[0005] In addition, from the perspective of battery safety performance, the extremely good thermal and electrical conductivity between the negative electrode active material and the copper foil allows for rapid heat and electrical conduction between the negative electrode active material and the copper foil when an internal short circuit or thermal runaway occurs, causing the thermal runaway area to spread rapidly to other areas.
[0006] Therefore, how to improve the fast charging and long life performance of lithium-ion batteries is a technical problem in this field. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a current collector, an electrode plate and a lithium ion battery.
[0008] The present invention adopts the following technical solutions: In a first aspect, the present invention provides a current collector, comprising: A current collector body and an auxiliary coating layer formed on both sides of the current collector body; The auxiliary coating comprises an ion conductive agent, a carbon material conductive agent and a binder; The ion conductive agent is MxOy, where M is any one or more of Mg, Al, Si, Ca, Ti, and Zr; The mass ratio of the ion conductive agent to the carbon material conductive agent is 0.2-20.
[0009] The present invention selects a combination of ionic conductive agent and carbon material conductive agent as auxiliary coating raw materials, which helps to solve the problem that pure carbon material conductive agent will participate in battery reaction, resulting in reduced battery capacity and reduced cycle performance. At the same time, the mixture of ionic conductive agent and carbon material conductive agent can control the short-circuit current, thereby controlling the thermal runaway of the battery.
[0010] The present invention can improve the contact strength between the active material and the current collector and improve the wettability of the electrolyte by coating the auxiliary coating on both sides of the current collector body, which helps to reduce the amount of binder, reduce the electrode impedance, and improve the fast charging performance and low temperature performance of the battery. At the same time, the auxiliary coating can increase the thickness of the active material layer formed on the surface of the current collector, solve the problem of demoulding and powder falling during coating due to the thick active material layer, and achieve the effect of improving battery stability and energy density.
[0011] The present invention limits the mass ratio of the ion conductive agent to the carbon material conductive agent to 0.2~20; when the mass ratio is too large, the impedance between the active material and the current collector is too large, resulting in excessive resistance of the battery; when the mass ratio is too small, the initial charge and discharge efficiency of the battery will be affected, and the cycle capacity retention rate of the battery will be reduced.
[0012] Specifically, as an embodiment of the present invention, the mass ratio of the ion conductive agent to the carbon material conductive agent is 0.2, 0.5, 0.7, 0.8, 0.9, 1, 1.2, 1.4, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or a range consisting of any two of these values. Preferably, the mass ratio of the ion conductive agent to the carbon material conductive agent is 4 to 15.
[0013] Furthermore, the thickness of the auxiliary coating formed on both sides of the current collector body is independently 0.3~30μm. If the thickness of the auxiliary coating is too large, it will affect the internal space utilization of the battery; if the thickness of the auxiliary coating is too small, its manufacturing process is too difficult. Specifically, as an embodiment of the present invention, the thickness of the auxiliary coating formed on both sides of the current collector body is independently 0.3μm, 0.5μm, 1μm, 1.5μm, 2μm, 3μm, 5μm, 7μm, 9μm, 10μm, 12μm, 15μm, 18μm, 20μm, 22μm, 24μm, 25μm, 27μm, 28μm, 30μm or a range consisting of any two of these values; preferably, the thickness of the auxiliary coating formed on both sides of the current collector body is independently 7~20μm.
[0014] Further, the oil absorption value of the ion conductive agent is greater than 100ml / 100g. If the oil absorption value is too low, it will not have an infiltration effect on the electrolyte. Specifically, in some embodiments of the present invention, the oil absorption value of the ion conductive agent is 100ml / 100g, 120ml / 100g, 130ml / 100g, 150 ml / 100g, 200ml / 100g, 250ml / 100g, 270ml / 100g, 300ml / 100g, 350ml / 100g, 400ml / 100g, 450ml / 100g, 500ml / 100g, 600ml / 100g, 700ml / 100g, 800ml / 100g or a range consisting of any two of these values. Preferably, the oil absorption value of the ion conductive agent is 120~1000ml / 100g. If the oil absorption value is too high, the cost will be too high and it will also cause difficulties in formulation and coating.
[0015] Furthermore, the carbon material conductive agent includes one or more of carbon black, acetylene black, graphene, carbon nanotubes, and Ketjen black.
[0016] Furthermore, the binder is selected from any one or more of PVDF, SBR, CMC, and PAA.
[0017] Specifically, in some embodiments of the present invention, the current collector body includes a metal material that can conduct electrons. Preferably, the current collector body includes one or more of aluminum, nickel, tin, copper, and stainless steel.
[0018] In a second aspect, the present invention provides an electrode plate, comprising the above-mentioned current collector and an active material layer coated on the surface of the current collector.
[0019] Since the content of the binder in the active material layer will affect the charge and discharge performance and low-temperature performance of the active material, the electrode plate of the present invention can reduce the content of the binder in the active material layer by selecting the above-mentioned current collector with an auxiliary coating, thereby reducing the electrode impedance and improving the fast charging performance, low-temperature performance and cycle performance of the battery.
[0020] Specifically, in some embodiments of the present invention, the conductive agent and the second binder in the active material layer can use conventional conductive agents and binders. The second binder includes polyvinylidene fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ether, copolymers of ethylene-tetrafluoroethylene, copolymers of vinylidene fluoride-tetrafluoroethylene, copolymers of vinylidene fluoride-trifluoroethylene, copolymers of vinylidene fluoride-trichloroethylene, copolymers of vinylidene fluoride-fluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, thermoplastic resins such as polyethylene and polypropylene; acrylic resin; and one or more of styrene butadiene rubber. The conductive agent includes one or more of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0021] Further, the electrode plate is a positive electrode plate, the active material is a positive electrode active material, and the positive electrode active material is selected from at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, and nickel manganese spinel; and / or, The electrode plate is a negative electrode plate, the active material is a negative electrode active material, and the negative electrode active material is selected from at least one of natural graphite, artificial graphite, mesophase carbon microspheres, lithium titanate, silicon alloy, tin alloy, and active lithium metal.
[0022] In a third aspect, the present invention further provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet and / or the negative electrode sheet is the above-mentioned electrode sheet.
[0023] The current collector of the present invention can improve the contact strength between the active material and the current collector and improve the wettability of the electrolyte by coating the auxiliary coating on both sides of the current collector body, which helps to reduce the amount of electrode plate binder, reduce electrode impedance, and improve the fast charging performance and low temperature performance of the battery. At the same time, the combination of ion conductive agent and carbon material conductive agent is selected as the auxiliary coating raw material, which helps to solve the problem of reduced battery capacity and reduced cycle performance caused by the participation of pure carbon material conductive agent in battery reaction, and effectively improves the fast charging performance, low temperature performance and cycle performance of lithium ion batteries. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0025] Example 1
[0026] The method for preparing a lithium-ion battery in this embodiment comprises the following steps: 1) Preparation of negative electrode The weight ratio of the negative electrode material is: 96.5% of artificial graphite, 1.50% of sodium hydroxymethyl cellulose CMC, 1.00% of carbon black conductive agent SP, and 1% of styrene-butadiene rubber SBR.
[0027] Then, they are dispersed in deionized water to obtain negative electrode slurry, which is coated on both sides of the negative electrode current collector, dried, rolled and vacuum dried, and welded with nickel lead wires using an ultrasonic welder to obtain a negative electrode sheet.
[0028] Among them, the copper foil in the negative electrode current collector is the current collector body, and an auxiliary coating is coated on both sides of the copper foil. The auxiliary coating includes an ion conductive agent Al2O3, a carbon material conductive agent carbon black and a binder polyacrylic acid PAA. The mass ratio of the ion conductive agent to the carbon material conductive agent is 5. The thickness of the auxiliary coating formed on both sides of the current collector body is independently 2μm, and the oil absorption value of the ion conductive agent is 250 ml / 100g.
[0029] 2) Preparation of positive electrode Lithium iron phosphate, conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF) were mixed evenly in a mass ratio of 96:2:2, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry. The slurry was evenly coated on both sides of the aluminum foil, and after drying, rolling and vacuum drying, a positive electrode material layer was obtained, and an aluminum lead wire was welded with an ultrasonic welder to obtain a positive electrode sheet.
[0030] 3) Preparation of electrolyte Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 3:7, and then lithium hexafluorophosphate (LiPF6) was added to a molar concentration of 1.0 mol / L.
[0031] 4) Battery assembly: A three-layer separator with a thickness of 20 μm is placed between the positive electrode sheet and the negative electrode sheet, and then the positive electrode sheet, the negative electrode sheet and the separator are assembled into a soft-pack battery cell; an aluminum-plastic film material is selected for packaging and molding the outer shell, and then the electrolyte injection, aging, formation, capacity division and other processes are carried out respectively to obtain a lithium-ion battery.
[0032] Example 2 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The mass ratio of Al2O3 to carbon black is 10.
[0033] Example 3 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The mass ratio of Al2O3 to carbon black is 4.
[0034] Example 4 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The mass ratio of Al2O3 to carbon black is 15.
[0035] Example 5 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The mass ratio of Al2O3 to carbon black is 0.2.
[0036] Example 6 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The mass ratio of Al2O3 to carbon black is 20.
[0037] Example 7 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The oil absorption value of Al2O3 is 120.
[0038] Example 8 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The oil absorption value of Al2O3 is 470.
[0039] Example 9 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The oil absorption value of Al2O3 is 1050.
[0040] Example 10 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The oil absorption value of Al2O3 is 95.
[0041] Embodiment 11 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The thickness of the auxiliary coating layer formed on both sides of the copper foil was independently 7 μm.
[0042] Example 12 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The thickness of the auxiliary coating layer formed on both sides of the copper foil was independently 20 μm.
[0043] Example 13 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The thickness of the auxiliary coating layer formed on both sides of the copper foil was independently 0.3 μm.
[0044] Embodiment 14 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The thickness of the auxiliary coating layer formed on both sides of the copper foil was independently 30 μm.
[0045] Embodiment 15 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The thickness of the auxiliary coating layer formed on both sides of the copper foil was independently 0.1 μm.
[0046] Example 16 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The thickness of the auxiliary coating layer formed on both sides of the copper foil was independently 32 μm.
[0047] Embodiment 17 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The ion conductive agent is MgO.
[0048] Embodiment 18 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The ion conductive agent is SiO2.
[0049] Embodiment 19 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The ion conductive agent is CaO.
[0050] Embodiment 20 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The ion conductive agent is TiO2.
[0051] Embodiment 21 This embodiment is basically the same as the embodiment 1, the only difference being the negative electrode current collector, specifically: The ion conductive agent is ZrO2.
[0052] Embodiment 22 The method for preparing a lithium-ion battery in this embodiment comprises the following steps: 1) Preparation of negative electrode The weight ratio of the negative electrode material is: 96.5% of artificial graphite, 1.50% of sodium hydroxymethyl cellulose CMC, 1.00% of carbon black conductive agent SP, and 1% of styrene-butadiene rubber SBR.
[0053] Then, they are dispersed in deionized water to obtain negative electrode slurry, which is coated on both sides of copper foil, dried, rolled and vacuum dried, and welded with nickel lead wires using an ultrasonic welder to obtain negative electrode sheets.
[0054] 3) Preparation of positive electrode Lithium iron phosphate, conductive agent and binder polyvinylidene fluoride (PVDF) were mixed evenly in a mass ratio of 96:2:2, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry. The slurry was evenly coated on both sides of the current collector, and after drying, rolling and vacuum drying, a positive electrode material layer was obtained, and an aluminum lead wire was welded with an ultrasonic welder to obtain a positive electrode sheet.
[0055] Among them, the aluminum foil in the positive electrode current collector is the current collector body, and auxiliary coatings are coated on both sides of the aluminum foil. The auxiliary coatings include ion conductive agent Al2O3, carbon material conductive agent carbon black and binder polyacrylic acid PAA. The mass ratio of the ion conductive agent to the carbon material conductive agent is 5. The thickness of the auxiliary coatings formed on both sides of the current collector body is independently 2μm, and the oil absorption value of the ion conductive agent is 250 ml / 100g.
[0056] 4) Preparation of electrolyte: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 3:7, and then lithium hexafluorophosphate (LiPF6) was added to a molar concentration of 1.0 mol / L.
[0057] 5) Battery Assembly: A three-layer separator with a thickness of 20 μm is placed between the positive electrode sheet and the negative electrode sheet, and then the positive electrode sheet, the negative electrode sheet and the separator are assembled into a soft-pack battery cell; an aluminum-plastic film material is selected for packaging and molding the outer shell, and then the electrolyte injection, aging, formation, capacity division and other processes are carried out respectively to obtain a lithium-ion battery.
[0058] Embodiment 23 The method for preparing a lithium-ion battery in this embodiment comprises the following steps: 1) Preparation of negative electrode The weight ratio of the negative electrode material is: 96.5% of artificial graphite, 1.50% of sodium hydroxymethyl cellulose CMC, 1.00% of carbon black conductive agent SP, and 1% of styrene-butadiene rubber SBR.
[0059] Then, they are dispersed in deionized water to obtain negative electrode slurry, which is coated on both sides of the current collector, dried, rolled and vacuum dried, and welded with nickel lead wires using an ultrasonic welder to obtain negative electrode sheets.
[0060] Among them, the copper foil in the negative electrode current collector is the current collector body, and an auxiliary coating is coated on both sides of the copper foil. The auxiliary coating includes an ion conductive agent Al2O3, a carbon material conductive agent carbon black and a binder polyacrylic acid PAA. The mass ratio of the ion conductive agent to the carbon material conductive agent is 5. The thickness of the auxiliary coating formed on both sides of the current collector body is independently 2μm, and the oil absorption value of the ion conductive agent is 250 ml / 100g.
[0061] 3) Preparation of positive electrode Lithium iron phosphate, conductive agent and binder polyvinylidene fluoride (PVDF) were mixed evenly at a mass ratio of 97:2:1, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry. The slurry was evenly coated on both sides of the current collector, and after drying, rolling and vacuum drying, a positive electrode material layer was obtained, and an aluminum lead wire was welded with an ultrasonic welder to obtain a positive electrode sheet.
[0062] Among them, the aluminum foil in the positive electrode current collector is the current collector body, and auxiliary coatings are coated on both sides of the aluminum foil. The auxiliary coatings include ion conductive agent Al2O3, carbon material conductive agent carbon black and binder polyacrylic acid PAA. The mass ratio of the ion conductive agent to the carbon material conductive agent is 5. The thickness of the auxiliary coatings formed on both sides of the current collector body is independently 2μm, and the oil absorption value of the ion conductive agent is 250 ml / 100g.
[0063] 4) Preparation of electrolyte: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 3:7, and then lithium hexafluorophosphate (LiPF6) was added to a molar concentration of 1.0 mol / L.
[0064] 5) Battery Assembly: A three-layer separator with a thickness of 20 μm is placed between the positive electrode sheet and the negative electrode sheet, and then the positive electrode sheet, the negative electrode sheet and the separator are assembled into a soft-pack battery cell; an aluminum-plastic film material is selected for packaging and molding the outer shell, and then the electrolyte injection, aging, formation, capacity division and other processes are carried out respectively to obtain a lithium-ion battery.
[0065] Comparative Example 1 This comparative example is basically the same as Example 1, except that the negative electrode current collector only includes copper foil and does not include an auxiliary coating.
[0066] Specifically, the preparation of the negative electrode sheet includes: The weight ratio of the negative electrode material is: 96.5% of artificial graphite, 1.50% of sodium hydroxymethyl cellulose CMC, 1.00% of carbon black conductive agent SP, and 1% of styrene butadiene rubber SBR.
[0067] Then, they are dispersed in deionized water to obtain negative electrode slurry, which is coated on both sides of copper foil, dried, rolled and vacuum dried, and welded with nickel lead wires using an ultrasonic welder to obtain negative electrode sheets.
[0068] Comparative Example 2 This comparative example is basically the same as Example 1, except that the negative electrode current collector only includes copper foil and does not contain an auxiliary coating; and the content of negative electrode binder SBR in the negative electrode active material layer is 2%.
[0069] Specifically, the preparation of the negative electrode sheet includes: The weight ratio of the negative electrode material is: 95.5% of artificial graphite, 1.50% of sodium hydroxymethyl cellulose CMC, 1.00% of carbon black conductive agent SP, and 2% of styrene butadiene rubber SBR.
[0070] Then, they are dispersed in deionized water to obtain negative electrode slurry, which is coated on both sides of copper foil, dried, rolled and vacuum dried, and welded with nickel lead wires using an ultrasonic welder to obtain negative electrode sheets.
[0071] Comparative Example 3 This comparative example is basically the same as Example 1, except that in the negative electrode current collector, the auxiliary coating only includes the carbon material conductive agent carbon black and the first binder SBR, and does not contain the ion conductive agent Al2O3.
[0072] Comparative Example 4 This comparative example is basically the same as Example 1, except that the negative electrode current collector is different, specifically: The mass ratio of Al2O3 to carbon black is 0.1.
[0073] Comparative Example 5 This comparative example is basically the same as Example 1, except that the negative electrode current collector is different, specifically: The mass ratio of Al2O3 to carbon black is 2:1.
[0074] The lithium ion batteries prepared in the examples and comparative examples were subjected to performance tests as follows: Note: The currents involved in the following test methods are all expressed as xC, where x is a number and C represents the nominal capacity of the battery. For example, a charging current of a battery with a nominal capacity of 1Ah of 0.5C represents 0.5×1=0.5A, and 6C represents 6×1=6A.
[0075] 1. Four-probe electrode resistance ① Take the rolled electrode sample, stick a 50μm thick high-temperature tape on the surface of the electrode dressing, and roll it back and forth 5 times with a 2kg roller to ensure that the tape and the electrode dressing are well adhered and flat without bubbles; ② Peel off the electrode attached to the high-temperature tape, and obtain a sample with the dressing attached to the tape; ③ Use a φ14mm sampler to cut the sample in ② into several small discs for testing; ④ Test and record the thickness of each small disc in ③; ⑤ Aim the four-probe probe at the center of the small disc, input the sample diameter, thickness and other information on the equipment software, and adjust the test range and current value on the equipment according to the equipment prompts; ⑥ Click Test to get the resistivity value of the sample being tested.
[0076] 2. Pole peel strength test ① Cutting the electrode: Cut the electrode into strips with a width of 28mm and a length ≥200mm.
[0077] ② Use a steel roller to roll parallel to the double-sided tape for 4-5 times, then tear off the anti-sticking layer of the double-sided tape, and stick the electrode strip sample parallel to the double-sided tape (the length direction of the electrode is consistent with the length direction of the steel plate and is centered), with one end of the electrode protruding from the steel plate. Use a steel roller to roll repeatedly for 4-5 times, then slowly flip the electrode protruding from the steel plate by 180° until a small part of the electrode is peeled off by the tape, then fix the lower end of the steel plate to the lower clamping point of the peel strength tester, and fix the flipped electrode to the upper clamping point of the peel strength tester, and keep the electrode and steel plate parallel to each other and perpendicular to the plane.
[0078] ③ After the electrode is fixed, first lower the upper clamping arm appropriately, return the tension parameter to zero, and then start testing the peel strength.
[0079] 3. Initial charge and discharge efficiency ④Charging process: 0.05C constant current charging for 60 minutes; 0.1C constant current charging for 60 minutes; 0.2C constant current charging for 120 minutes; ⑤ Capacity division step: 0.33C constant current constant voltage charging to 3.8V, 0.05C cut-off; 0.33C discharge to 2.0V; ⑥First charge and discharge efficiency = 0.33C discharge capacity / (0.05C charge capacity + 0.1C charge capacity + 0.2C charge capacity + 0.33C constant current and constant voltage charge capacity) × 100%.
[0080] 4.6C constant current charging test and temperature test ① Stick the temperature probes to the positive ear, negative ear, and battery surface to test and record the temperature at each location; ② Place the battery in a 25℃ environment for 3 hours; ③0.33C constant current discharge to 2.0V, leave for 30 minutes; ④6C constant current charge to 3.8V, leave for 30 minutes; ⑤Record the 6C charging curve and the temperature change curve at each position.
[0081] 5.55℃ cycle test ① Place the soft-pack battery in a 55°C environment for 3 hours; ②1C constant current and constant voltage charging to 3.8V, 0.05C cut-off; leave for 30 minutes; ③1C constant current discharge to 2.0V; leave for 30 minutes; ④Cycle steps ②~③; ⑤ Repeat this cycle for 500 times, and record the first discharge capacity and the last discharge capacity. Calculate the capacity retention rate of the cycle according to the following formula: Battery capacity retention rate (%) = last discharge capacity / first discharge capacity × 100%.
[0082] The performance test results of various embodiments and comparative examples are shown in Tables 1-5.
[0083] Table 1 Experimental comparison of different mass ratios of Al2O3 and carbon black
[0084] From the test results of Examples 1-6 and Comparative Examples 3-5 in Table 1, it can be seen that the current collector of the present invention has an auxiliary coating, and a combination of an ion conductive agent and a carbon material conductive agent is selected as the auxiliary coating raw material, and the mass ratio of the ion conductive agent to the carbon material conductive agent is limited to 0.2~20, which can improve the contact strength between the active material and the current collector and improve the wetting performance of the electrolyte, help reduce the amount of binder, reduce electrode impedance, and improve the fast charging performance and low temperature performance of the battery. When the mass ratio of the ion conductive agent to the carbon material conductive agent is less than 0.2, the first charge and discharge efficiency and the 55-degree cycle capacity retention rate are both low; and when the mass ratio of the ion conductive agent to the carbon material conductive agent is greater than 20, the impedance between the active material and the current collector is too large, resulting in excessive resistance of the battery.
[0085] Table 2 Experimental comparison of oil absorption values of different Al2O3
[0086] From the test results of Example 1 and Examples 7-10 in Table 2, it can be seen that the greater the oil absorption value of the ion conductive agent, the higher the high-rate charging ratio of the battery, but when the oil absorption value is greater than 1000, the cost increases sharply. Preferably, the oil absorption value of the ion conductive agent is 120-1000 ml / 100 g.
[0087] Table 3 Experimental comparison of different auxiliary coating thicknesses
[0088] It can be seen from the test results of Example 1 and Examples 11-16 in Table 3 that when the thickness of the auxiliary coating formed on both sides of the current collector body is too low, the peel strength is obviously weak; and when the thickness of the auxiliary coating is too high, the initial charge and discharge efficiency is significantly reduced, resulting in a reduction in battery capacity.
[0089] Table 4 Experimental comparison of ionic conductive agents of different materials
[0090] It can be seen from the test results of Example 1 and Examples 17-21 in Table 4 that for different types of MxOy ion conductive agents, as long as the mass ratio of the ion conductive agent to the carbon material conductive agent meets the corresponding conditions, the impedance of the obtained electrode plates is low, and the battery high temperature cycle performance and the first charge and discharge efficiency are not much different, indicating that different types of ion conductive agents can achieve corresponding effects as auxiliary coatings.
[0091] Table 5 Experimental comparison of different positive and negative electrode formulations
[0092] From the test results of Example 1, Examples 22-23 and Comparative Examples 1-2 in Table 5, it can be seen that the use of the current collector coating of the present invention can effectively increase the peel strength of the positive and negative electrodes, regardless of whether it is the positive electrode or the negative electrode. Under the same peel strength, in the case of the auxiliary coating, the amount of binder used in the positive and negative electrodes can be reduced.
[0093] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.
Claims
1. A current collector, characterized in that: include: A current collector body and an auxiliary coating layer formed on both sides of the current collector body; The auxiliary coating comprises an ion conductive agent, a carbon material conductive agent and a binder; The ion conductive agent is MxOy, where M is any one or more of Mg, Al, Si, Ca, Ti, and Zr; The mass ratio of the ion conductive agent to the carbon material conductive agent is 0.2-20.
2. The current collector according to claim 1, characterized in that: The thickness of the auxiliary coating layer formed on both sides of the current collector body is independently 0.3-30 μm.
3. The current collector according to claim 1, characterized in that: The oil absorption value of the ion conductive agent is greater than 100 ml / 100 g.
4. The current collector according to claim 1, characterized in that: The carbon material conductive agent includes one or more of carbon black, acetylene black, graphene, carbon nanotubes, and Ketjen black.
5. The current collector according to claim 1, characterized in that: The binder is selected from any one or more of PVDF, SBR, CMC and PAA.
6. An electrode plate, characterized in that: The invention comprises the current collector according to any one of claims 1 to 5 and an active material layer coated on the surface of the current collector.
7. The electrode plate according to claim 6, characterized in that: The electrode plate is a positive electrode plate, the active material is a positive electrode active material, and the positive electrode active material is selected from at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, and nickel manganese spinel; and / or, The electrode plate is a negative electrode plate, the active material is a negative electrode active material, and the negative electrode active material is selected from at least one of natural graphite, artificial graphite, mesophase carbon microspheres, lithium titanate, silicon alloy, tin alloy, and active lithium metal.
8. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet and / or the negative electrode sheet is the electrode sheet according to any one of claims 6-7.
Citation Information
Patent Citations
Anode or cathode pole piece of lithium ion battery and coating method thereof
CN101174685A
Multifunctional coating and slurry for lithium ion battery, preparation methods for multifunctional coating and slurry, and lithium ion battery
CN106229474A
Positive pole piece, secondary battery, battery module, battery pack and electric device
CN116964766A
Electrode plate and lithium ion battery
CN119008957A
